2018
DOI: 10.1111/evo.13648
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary stability of the lysis‐lysogeny decision: why be virulent?

Abstract: Lytic viruses infect and kill host cells, producing a large number of viral copies. Temperate viruses, in contrast, are able to integrate viral genetic material into the host cell DNA, leaving a viable host cell. The evolutionary advantage of this strategy, lysogeny, has been demonstrated in complex environments that include spatial structure, oscillating population dynamics, or periodic environmental collapse. Here, we examine the evolutionary stability of the lysis–lysogeny decision, that is, we predict the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 37 publications
(66 reference statements)
5
47
0
Order By: Relevance
“…(4A) -red, purely lytic strategy is robust). This finding agrees with multiple recent studies of the evolution of viral strategies given long-term viral-host feedback (15,23,24). We also note that invasion by a mutant strain does not necessarily imply replacement of the resident strain.…”
Section: Endemically Infected States and Viral Invasionsupporting
confidence: 93%
See 1 more Smart Citation
“…(4A) -red, purely lytic strategy is robust). This finding agrees with multiple recent studies of the evolution of viral strategies given long-term viral-host feedback (15,23,24). We also note that invasion by a mutant strain does not necessarily imply replacement of the resident strain.…”
Section: Endemically Infected States and Viral Invasionsupporting
confidence: 93%
“…For each temperate phage model, we construct the mutant-resident system, and compute the invasion fitness of mutant viral strains at the resident endemic equilibrium via a next-generation matrix approach (22,23); see SI Text, section 4.…”
Section: Endemic Invasion Analysismentioning
confidence: 99%
“…The accuracy of the model could be improved by adding the molecular mechanisms leading to the formation of new lysogens, which has been modeled at single strain-level but proven hard to incorporate into ecological scenarios (Steward and Levin 1984; Wang and Goldenfeld 2010; Maslov and Sneppen 2017; Wahl et al 2018; Weitz et al 2019; Chaudhry et al 2019). The accuracy could be also improved by incorporating by incorporating specific predator and immune system pressure (Thingstad and Lignell 1997; Thingstad 2000; Winter et al 2010; Dwayne et al 2017; Caron et al 2017; Talmy et al 2019), variable energy sources (Thingstad and Lignell 1997; Weitz et al 2015), and ecosystem-specific ranges for phage-bacteria traits and nested viral-microbial networks (Flores et al 2011; Thingstad et al 2014; Gao et al 2017; Hendricks 1972; Kirchman 2016; De Paepe and Taddei 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these model predictions, a combination of modelling and experimental work showed that selection pressures on phage virulence change over the course of an epidemic, favouring a virulent phage strain early on, when the density of susceptible cells is high, but a less virulent (i.e., lysogenic) phage strain later in the epidemic, when susceptible cells have become scarce [13,14]. Other modelling work has shown that if phages, lysogenised cells, and susceptible cells coexist for long periods of time, the susceptible cell density becomes low because of phage exploitation, and less and less virulent phages are selected [15,16].Erez et al [9] propose that the arbitrium system may have evolved to allow phages to cope with the changing environment during an epidemic, allowing the phages to exploit available susceptible bacteria through the lytic cycle when few infections have so far taken place and hence the concentration of arbitrium is low, while entering the lysogenic cycle when many infections have taken place and the arbitrium concentration has hence increased. This explanation resembles results for other forms of phage-phage interaction previously found in Escherichia coli -infecting phages [17,18].…”
mentioning
confidence: 99%
“…Free phage particles decay at a rate δ and adsorb to bacteria at a rate a. Adsorptions to lysogens result in the decay of the infecting phage, thus describing the well-known effect of superinfection immunity [25][26][27][28][29], while adsorptions to susceptible bacteria result in infections with success probability b. We consider the lytic cycle to be fast compared to both bacterial growth and the lysogenic cycle (c.f., [11,13,16,24]), so that a lytic infection can be modelled as immediate lysis releasing a burst of B free phages. Since the genes encoding arbitrium production are among the first genes to be expressed when a phage…”
mentioning
confidence: 99%